Revista ACB Vol. 18, n. 2 (2013) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
Revista ACB Vol. 18, n. 2 (2013)Link de acesso ao númerohttp://revistaacb.emnuvens.com.br/racb/issue/view/52